ACUTE RESPIRATORY VIRAL INFECTIONS IN KAZAKHSTAN IN 2017-2019 - Klivleyeva N.G.; Lukmanova G.V.; Saktaganov N.T.; Sayatov M.H.; Glebova T.I.; Ongarbayeva N.S.; Baimukhametova A.M.; Shamenova M.G.; Berezin V.E.; Nusupbaeva G.E.; Aikimbayev A.M. (Scientific Journal of Pedagogy and Economics, 2020)
During the 2017-2019 period, 4,391 clinical samples were collected from patients diagnosed with ARVI, ARI, bronchitis, and pneumonia in polyclinics and healthcare facilities located in various regions of Kazakhstan. Laboratory diagnosis of 4,391 nasopharyngeal swabs in the real-time polymerase chain reaction revealed the genetic material of pathogens causing ARVI in 24.41 % of cases, including adenovirus in 1.78 %, rhinovirus in 4.34 %, coronavirus in 0.82 %, parainfluenza virus type I/III in 0.87 %, metapneumovirus in 1.04 %, bokavirus in 0.30 % of examined samples. The number of samples tested positive for respiratory syncytial virus was the highest (15.25 %). The data obtained from screening of nasopharyngeal swabs in the real-time polymerase chain reaction suggested the circulation of ARVI of mixed etiology in the examined areas of the RK. The results of the primary screening of clinical samples collected from various regions of Kazakhstan during the epidemic seasons 2017-2019 in the polymerase chain reaction correlate with the data obtained over the 2016-2017 epidemic season according to the spectrum of influenza and ARVI causative agents. Co-circulation of adenovirus, rhinovirus, coronavirus, type I/III parainfluenza virus, metapneumovirus, bocavirus is continuing with the predominant prevalence of the respiratory syncytial infection pathogen, the proportion of which was 15.25 % of the total number of samples. Differential diagnosis of ARVI contributes to the timely identification of infectious agents in humans and more effective implementation of sanitary and preventive measures.